Effects of environment and seedling age on growth and transplanting quality of hybrid indica rice seedling - Zhao Min; Zhong Xiaoyuan; Tian Qinglan; Liu Bo; Sun Hong; Hu Hui; Yang Yunjie; Ren Wanjun (浙江大学学报. 农业与生命科学版)
Environmental factors such as light, temperature and humidity, play important roles in rice growth. Greenhouse is an emerging seedling cultivation environment different from field, and it is a scant sunlight environment with temperature and humidity different from field. Planting mechanization has strict seedling age for morphological differences. Little research has been done on the effects of seedling age and substrate on rice seedlings in greenhouse. Therefore, this study has the aim to investigate the effects of seedling age and substrate on growth and transplanting quality of hybrid indica rice seedling in greenhouse.The experiment was designed in three-factor split plot by using Fyou 498 as material. Comparing meteorological characteristics of the two seedbed, effects of Heng Aoda and nutrient soil and different seedling ages with 20, 30 and 40 d on seedling quality and transplanting quality of hybrid indica rice were studied.The main results were as follows: 1) The temperature, relative humidity and light intensity of greenhouse seedbed were similar to these of field seedbed, and diurnal variation in temperature, relative humidity and light intensity of greenhouse seedbed lagged behind these of field seedbed. Light intensity of greenhouse seedbed was lower than field seedbed and temperature of greenhouse seedbed was higher than field seedbed.2) The seedling growth in greenhouse was two segments with fast early and slow rear, and its rate of empty hills and rate of float hills were 4.29% and 2.73% lower than these of field seedbed when transplanted, respectively. The seedling in greenhouse had a better transplanting quality, and the number of plants per hill was 22.22% higher than that in field seedbed. 3) The seedling with 30 d seedling age was suitable for planting mechanization for the lowest rate of empty hills and the highest number of plants per hill. However, the seedling with 40 d seedling age had poor transplanting quality for the highest rate of empty hills, the highest rate of injury hills, the highest rate of float hills and the lowest number of plants per hill. The seedling in greenhouse could be suitable for long seedling age by properly controlling seedling growth with temperature, relative humidity and light intensity regulation to increase scope of seedling age for planting mechanization. 4) The nutrient soil seeding had better transplanting quality than Heng Aoda seeding with high rate of empty hills and high rate of float hills, but substrate seeding had small injury for its loose property on planting mechanization. Thus, the substrate was considered to support seeding in greenhouse for low rate of injury hills by further research. 5) The temperature, relative humidity and light intensity had an impact on seedling quality and transplanting quality including a great effect of temperature on leaf area, leaf age and dry mass, and accumulated temperature was significantly correlated with the leaf age. The temperature, relative humidity and light intensity had an impact on rate of float hills and number of plants per hill and was not significantly correlated with the rate of empty hills and rate of injury hills.